The efficacy of resveratrol supplementation on inflammation and oxidative stress in type-2 diabetes mellitus patients: randomized double-blind placebo meta-analysis - Peiye Zhu; Yunrui Jin; Jiya Sun; Xia Zhou (Frontiers in Endocrinology)
BackgroundThe effects of resveratrol supplementation on inflammation and oxidative stress in patients with type 2 diabetes mellitus (T2DM) were controversial. A meta-analysis was performed to assess the changes in levels of inflammation and oxidative stress in patients with T2DM.MethodsRelevant literatures before November 6, 2024 were screened through Web of Science,Embase,the Cochrane Library and other sources (ClinicalTrials, ProQuest Dissertations and Theses). The quality of the literature was evaluated according to the Cochrane Handbook of Systematic Reviews. The study quality was assessed using the risk-of-bias 2 tool and the Grading of Recommendations Assessment,Development and Evaluation (GRADE) system. Review Manager 5.3 conducted meta-analysis of the data included in the literature.ResultsThis meta-analysis was conducted in six randomized controlled trials involving 533 participants. Our results showed that supplementation with resveratrol significantly reduced C-reactive protein levels(SMD = -1.40, 95%CI(-2.60, -0.21), P = 0.02; Level of evidence: low), lipid peroxide levels (SMD = -0.99, 95%CI(-1.36, -0.61), P < 0.00001; Level of evidence: low), 8-isoprostanes(SMD = -0.79, 95%CI(-1.16, -0.42), P < 0.0001; Level of evidence: low) and oxidative stress score (SMD = -1.62, 95%CI(-2.49, -0.75), P = 0.0003; Level of evidence: very low). In addition, compared to placebo, Supplementation with resveratrol significantly increased glutathione peroxidase levels (SMD = 0.38, 95%CI(0.03, 0.74), P = 0.04; Level of evidence:low) and catalase levels (SMD = 0.33, 95%CI(0.03, 0.63), P = 0.03; Level of evidence: low). However, no significant difference was observed in improving interleukin-6 levels (SMD = -1.35, 95%CI(-2.75, -0.05), P = 0.06; Level of evidence: very low), tumor necrosis factor α levels (SMD = -3.30, 95%CI(-7.47, 0.87), P = 0.12; Level of evidence: very low), superoxide dismutase levels (SMD = 0.39, 95%CI(-0.26, 1.04), P = 0.24; Level of evidence: very low), total antioxidant capacity levels (SMD = 0.39, 95%CI(-0.23, 1.00), P = 0.21; Level of evidence: very low) and malondialdehyde levels (SMD = -3.36, 95%CI(-10.30, 3.09), P = 0.29; Level of evidence: very low).ConclusionResveratrol improved inflammation and oxidative stress in T2DM patients to some extent. This provides a new idea and method for clinical treatment. However, due to the limitations of the study, more large-sample, multi-center clinical studies are needed to verify this conclusion.